Filling the gaps. Issue 6 (1st December 2022) - Beggan, Ciarán
Abstract : Magnetic field variations in the wake of geomagnetic storms may affect critical infrastructure. Ciarán Beggan explains how three new variometers will help to monitor the situation. Abstract: Magnetic field variations in the wake of geomagnetic storms may affect critical infrastructure. Ciarán Beggan explains how three new variometers will help to monitor the situation.